Occipito-cervical meningioma in pregnancy - Indiyarti, Riani (Faculty of Medicine, Trisakti University, 2008)
Meningiomas are tumors that are believed to be derived from the cells and vascular elements of the meninges, and grow intracranially or in the vertebral canal. They are most common in women. The growth of meningiomas is stimulated by female sex hormones and thus may progress more rapidly in pregnant women and in women with breast cancer. The patient was a pregnant 39-year old woman (G4P3A0) of 8 months gestation. The clinical symptoms and signs were progressive upper motor neuron quadriparesis, diminished sensory functions from the level of C2 downwards, and loss of bladder and rectal control. Brain and cervical computed tomography (CT) scans done 2 months before admission showed no abnormalities. Induced delivery was terminated by forceps extraction, resulting in a baby of 2,100 g with Apgar score 7/9. After delivery, postcontrast magnetic resonance imaging (MRI) showed a large contrast-enhancing tumor mass of intradural-extramedullary location in the right occipito-cervical region. The tumor had a meningeal tail, extended into the right posterior fossa and caudally to the level of C3, with compression of the spinal cord. The patient underwent a nontotal resection to remove a tumor that microscopically had the features of a meningioma.